2015
DOI: 10.1097/fjc.0000000000000208
|View full text |Cite
|
Sign up to set email alerts
|

AT2 Receptor Activities and Pathophysiological Implications

Abstract: Although angiotensin II subtype-2 receptor (AT2R) was discovered over two decades ago, its contribution to physiology and pathophysiology is not fully elucidated. Current knowledge suggests that under normal physiologic conditions, AT2R counterbalances the effects of angiotensin II subtype-1 receptor (AT1R). A major obstacle for AT2R investigations was the lack of specific agonists. Most of the earlier AT2R studies were performed using the peptidic agonist, CG42112A, or the non-peptidic antagonist PD123319. CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 92 publications
4
69
1
Order By: Relevance
“…These confusing results regarding AT2 receptor function is suggested to be largely dependent on expression levels of AT2 receptor in addition to Nox2 regulation and transforming growth factor beta 1 (TGFβ1) signaling pathways (17). The AT2 receptor will not be discussed further in this review, however, there are excellent review articles summarizing recent findings regarding the role of AT2 receptor in hypertension, vascular remodeling and cardiovascular dysfunction (9, 10, 18). …”
Section: Introductionmentioning
confidence: 99%
“…These confusing results regarding AT2 receptor function is suggested to be largely dependent on expression levels of AT2 receptor in addition to Nox2 regulation and transforming growth factor beta 1 (TGFβ1) signaling pathways (17). The AT2 receptor will not be discussed further in this review, however, there are excellent review articles summarizing recent findings regarding the role of AT2 receptor in hypertension, vascular remodeling and cardiovascular dysfunction (9, 10, 18). …”
Section: Introductionmentioning
confidence: 99%
“…Although the role of AT1R in the RAAS pathway is well-characterized, many of the physiological actions of AT2R have yet to be elucidated [91]. A peptide agonist, CGP42112A, has been known since 1989 [92], but lack of in vivo stability limited its use [93].…”
Section: Angii Type 2 Receptor Agonistsmentioning
confidence: 99%
“…6162 AngIII is the likely ligand for AT2R. 63 The Denton lab showed that direct stimulation of AT2R with the selective agonist C21 increases natriuresis and diuresis without changes in GFR or RBF, evidence for tubular actions.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Denton has demonstrated that the lower BP and more sensitive pressure natriuresis observed in WT female rodents is associated with 4 fold higher AT2R mRNA; 64 and that this sex advantage disappears with age and in global AT2R KO mice. 65 This fast growing area full of therapeutic potential 61,62 has a large gap in knowledge about how AT2R signaling affects sodium transporters/channels and intrarenal RAS in males and females.…”
Section: Summary and Future Directionsmentioning
confidence: 99%